FEATURES OF THE SECURITY SYSTEM OF THE ELECTRICITY MARKET IN UKRAINE - MATIICHUK, LIUBOMUR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The emergence of state-owned enterprises: "Market Operator" and "Guaranteed Buyer," which are responsible for the operation of the day-ahead and intraday market and form the price policy for payment of electricity services to producers and suppliers that use renewable energy sources, i.e., work according to "green tariff" and "regulated tariff" for the needs of the population.It was noted that energy is distributed within the UES by energy supply companies licensed to provide electric energy at regulated and non-regulated tariffs.It is outlined that the actual results of the processes of reforming the electricity market are: the organization of the electricity market segments, which allows us to consider the day-ahead market as the leading indicator of price formation; two trade zones operating at the same time - the United Energy System of Ukraine and the energy center of the Burshtyn TPP, where different prices have been formed due to the generation structure; the possibility of using the export potential of electricity according to the principles of ENSTO-S has been launched, which promotes general agreement between supplier countries, increases competition, forms a system of balanced results with the minimization of losses, accelerates the processes of integration of the electricity market of Ukraine into the European energy system.At the same time, the electricity market of Ukraine faces many challenges and threats, among which: the countdown to the implementation of the free electricity market model was not accompanied by objective reasons by changes in regulated electricity prices for specific categories of consumers (population) and cross-subsidization, which ultimately caused significant financial stress to the state-owned enterprises "Energoatom" and "UkrHydroEnergo," which are subject to the imposition of special duties; the practice of operating auctions for renewable energy sources in order to optimize their value is not implemented correctly. In this area, only the construction of such objects took place under the conditions of fixing the "green tariff"; the war in Ukraine led to a drop in economic development, significant consumer debt, and a decrease in electricity consumption, as a result of a drop in prices, an increase in the deficit and debt coverage for select categories of consumers; the significant accumulation of the debt burden of SE "Energorynok" in front of a significant number of generating companies, requires immediate state regulation and the adoption of a particular law regarding the further resolution of this problem; replacement of old capacities with new ones with a quick start for balancing and functioning of gas piston units and energy storage systems.It became known that in terms of its actual content, the electric power industry has several specific features that characterize its energy orientation: the change of parameters depending on the field of application, the simultaneity of the processes of production and consumption as an energy resource; constancy and identity of volumes of produced and consumed electrical energy; lack of possibilities for reservations in the form of goods; the impossibility of a predictable assessment of resource generation and consumption; complete dependence of the production component on consumer demand. In addition to the circumstances of the economic direction, specific properties are also characteristic of electric energy, which is related to its essential purpose as an energy resource: power; time; terms and conditions of consumption; quality; distance; variability.Today, the already existing positive and negative consequences of the effectiveness of state economic regulation of the electricity market should be noted. As for the negative consequences, it should be noted the versatile and non-uniform nature of the application of various forms and methods of pricing to electricity producers; tax imbalance due to the lack of necessary tax and budget levers for regulating the electricity industry; the practice of the system of cross-subsidization of some consumers at the expense of others through the wholesale market price (ORC) for electric energy.A review of safety criteria in the country's electric power sector shows the imperfection of the electricity market and the need to strengthen the relevant safety tools.
Keywords: electric energy; electric power industry; energy; electric power safety; energy market of Ukraine